Analysis of Physical Education Study Final Test Questions during the Pandemic Period in Class VIII of SMP Negeri 3 Bengkulu Tengah - Hevis Panji Pajri; Citra Dewi; Martiani Martiani (Penerbit Jurnal Indonesia, 2021)
This study aims to find out how the UAS questions in physical education lessons are made by sports teachers at SMP Negeri 3 Bengkulu Tengah. This research is a qualitative research. The subjects in this study were sports teachers who made UAS questions in class VII. The instruments in this research are content validity test instruments and construct validity tests. The results of the study show that the questions made by the sports teacher at SMP Negeri 3 in Central Bengkulu have not been said to be good. Because the teacher is not consistent in making questions for example in the content validity test. It is said on the grid of questions that are contained in the indicators totaling 10 but in fact only 5 items are contained in the indicators, and it is also said on the grid of questions that are contained in indicators from No. 1-10 while in fact on questions of No. 26 – 30 . on the items that are not contained in the lattice indicators totaling 25 items. Analysis of the questions on the construct validity test on the rules of writing a good question at No. 14 which contains each question must use language that is in accordance with the rules of the Indonesian language. In the problems analyzed, the researchers found that the writing on foreign language words was not italicized.